Social inclusion and violence prevention in psychiatric inpatient care. A qualitative interview study with service users, staff members and ward managers - Veikko Pelto-Piri; Lars Kjellin (BMC, 2021)
Abstract Background Many psychiatric services include social inclusion as a policy with the aim to offer users the opportunity to participate in care and to form reciprocal relationships. The aim of this study was to explore opportunities and problems with regard to participation, reciprocity and social justice that different stakeholders experience when it comes to social inclusion for service users and minimizing violence in psychiatric inpatient care. Methods Qualitative interviews were performed with 12 service users, 15 staff members, and six ward managers in three different kinds of psychiatric wards in Sweden. The data were analyzed using the framework method and qualitative content analysis, which was based on the three following social inclusion values: participation, reciprocity, and social justice. Results Themes and subthemes were inductively constructed within the three social inclusion values. For participation, staff and ward managers reported difficulties in involving service users in their care, while service users did not feel that they participated and worried about what would happen after discharge. Staff gave more positive descriptions of their relationships with service users and the possibility for reciprocity. Service users described a lack of social justice, such as disruptive care, a lack of support from services, not having access to care, or negative experiences of coercive measures. Despite this, service users often saw the ward as being safer than outside the hospital. Staff and managers reported worries about staffing, staff competence, minimizing coercion and violence, and a lack of support from the management. Conclusions By applying the tentative model on empirical data we identified factors that can support or disrupt the process to create a safe ward where service users can feel socially included. Our results indicate that that staff and service users may have different views on the reciprocity of their relationships, and that users may experience a lack of social justice. The users may, due to harsh living conditions, be more concerned about the risk of violence in the community than as inpatients. Staff and ward managers need support from the management to foster a sense of community in the ward and to implement evidence-based prevention programs.